Atomic layer deposition assisted fabrication of high-purity carbon nanocoil for electrochemical energy storage. (1st April 2018) - Yu, Lei; Wan, Gengping; Qin, Yong; Wang, Guizhen
Abstract: In this paper, we describe a novel and high-yield strategy to fabricate high-purity carbon nanocoils (CNCs) with Cu nanoparticles as catalysts produced by atomic layer deposition (ALD). The pristine CNCs display uniform structure and are rich of abundant functional groups, which is more beneficial to achieve high content of nitrogen doping. The high-content nitrogen-doped CNC exhibits improved electrical double-layer capacitive properties (143 F g −1 at 0.5 A g −1 ) over previously reported CNC-based electrode materials. Moreover, the carbonized CNC can act as conductive matrix to promote the electrochemical performance of metal oxides. The prepared NiO/CNC composites show high specific capacity (430 C g −1 at 1 A g −1 ), super rate capability and outstanding cycling stability. Ultimately, A hybrid supercapacitor assembled by using N-doping CNC as negative electrode and NiO/CNC as positive electrode, delivers a high energy density of 17.54 W h kg −1 at a power density of 849.56 W kg −1 and a high power density of 12.74 kW kg −1 at an energy density of 7.47 W h kg −1, along with desirable cycling lifetime. This work suggests that CNCs have great potential for the electrochemical energy storage devices. Graphical abstract: Highlights: We present a novel and facile strategy to fabricate high-purity carbon nanocoils. Carbon nanocoils with high content of N doping exhibit decent supercapacitive properties. Carbon nanocoils can enhance the electrochemical performance of NiO as battery-type electrodes.